Análisis del Estatuto para la aplicación de la Justicia Indígena en la comunidad Colorados del Peripa del cantón Santo Domingo, en el año 2022. - Serrano Ladino, Richar Iván ; Núñez Minaya, Oscar Rolando (2023)
This research focuses on being able to perform an analysis and understand the role that the Statute fulfills within the community Colorados del Peripa, for the application of indigenous justice based on their beliefs, traditions at the same time are recognized in the 2018 constitution of the Republic of Ecuador, and that solutions are given as an alternative measure when there is a problem with the members within the comun mentioned by members of the community that at present there are many shortcomings in the same context, within the regulation since it does not punish several crimes, and this does not allow a correct execution in terms of indigenous justice, in many cases they must go to the ordinary justice system and they do not agree with how their processes are carried out in this way. The lack of knowledge of the regulations by the community members is a detrimental factor so that in the course of time the statute has become partially obsolete, for this reason the purpose of this research is to determine which crimes are not sanctioned by the regulations within the community, and a strong lack of knowledge on the part of the authorities, leaders when following the protocol established by the community demands in the application of indigenous justice, but something very important must be taken into account since the statute that regulates the behavior of the members of the Tsachila community and tries to maintain the good living does not sanction. The communities keep track of the cases that are dealt with by the ordinary justice and the new authorities that over the years have come to the leadership as rulers of the Tsachila nationality have tried to reform the Statute, but no clear solutions have been given, however we can see the problem in the loss of identity as an indigenous nationality. On the other hand, this generates that the communities can be vulnerable for crimes or misdemeanors that are not sanctioned. It is believed that at present it is a factor which is 15 directly affecting the loss of their traditions, customs and beliefs, it should be mentioned that there are communities within the Tsachila nationality which have created rules with internal regulations governing these communities. The present investigation was developed under a mixed methodology, it was taken into account, the population, variable, sample, in the same way it is given a certain degree of significance to the statistics obtained as well as the results obtained where the current reality that the community of Peripa Colorados is going through is evidenced, also applied, bibliographic and field research was used. While it is true that both empirical and theoretical methods were used and interviews and surveys were applied as research methods for a better understanding of the topic and its development. Keywords Statute, Nationalities, Indigenous, Indigenous Justice, Ordinary Justice